Economic and socio-demographic analysis of marriage instability: A case study of Kwabre East District - Frimpong, Augustine Adu (2016)
A thesis submitted to the Department of Economics, Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Philosophy (Economics), 2013.